THU0103 Is Interleukin 17 Implicated in Osteoporosis Pathogenesis in Rheumatoid Arthritis? Relation between IL-17 Serum Level and Frax Index in Premenopausal Rheumatoid Arthritis Patients. (15th July 2016) - Aboeladl, N.A.; Koryem, H.K.; Rezk, M.A.; Hassan, M.M.; Eltawab, S.S.
Abstract : Background: Rheumatoid arthritis (RA) is one of the most common form of inflammatory arthritis. It is characterized by being chronic, progressive with systemic inflammation. Patients with RA are at an increased risk of osteoporosis (OP) and consequentaly osteoporotic fractures (OFs). Interleukin-17 (IL-17) is a cytokine expressed in inflammatory and autoimmune diseases. It plays an important role in the pathogenesis of RA and OP. Fracture Risk Assessment Tool (FRAX)is a computer-based algorithm used to measure the 10-year probability of a major osteoporotic fractures and the 10-year probability of hip fracture. Current studies focus on better assessment of risk factors of OFs in RA patients aiming to prevent them and their subsequent complications. Objectives: To study the correlation between serum IL-17 level and FRAX index scores in pre-menopausal RA patients. Methods: This study included 25 premenopausal RA patients and 20 healthy controls. Serum IL-17 level was measured by using ELISA technique, bone mineral density (BMD) measured using DEXA scan and FRAX index was calculated by using online FRAX calculator (Femoral neck BMD was used to enhance fracture risk prediction). Results: Serum IL-17 level among RA patients was significantly higher than healthy controls, (5.99 ± 1.22pg/ml), (3.73 ± 2.15pg/ml) respectively with a p <0.001. Serum IL-17 levels showed a positive significant correlation with the FRAX index scores in RA patients. Conclusions: IL-17 is highly suspected to be implicated in the pathogenesis of OP in RA patients which may spotlight that the emergence of IL 17 blockade as a future therapy in RA is to be highlighted. References: Kim SY, Schneeweiss S, Liu J, Daniel GW, Chang C-L, Garneau K, et al. Risk of osteoporotic fracture in a large population-based cohort of patients with rheumatoid arthritis. Arthritis Research & Therapy 2010; 12(4):R154. Sorbi R, Aghamirsalim M. Osteoporotic Fracture Program management: Who should be in charge? A comparative survey of knowledge in orthopaedic surgeons and internists. Orthop Traumatol Surg Res 2013; 99(6):723–30. Rosu A, Margaritescu C, Stepan A, Musetescu A, Ene M. IL-17 patterns in synovium, serum and synovial fluid from treatment-naive, early rheumatoid arthritis patients. Rom J Morphol Embryol 2012; 53(1):73–80. Kanis JA, Johnell O, Oden A, Johansson H, McCloskey EV.FRAX and the assessment of fracture probability in men and women from the UK. Osteoporos Int 2008; 19:385–97. Acknowledgement: Deep thanks to my professors, parents and my husband Disclosure of Interest: None declared